An examination of Canadian firms delisting from US exchanges - Jonathan Witmer (Bank of Canada, 2008)
This paper examines Canadian and other foreign firms that have been involuntarily delisted from major U.S. exchanges. I find that, for most countries, less than 10% of firms get delisted from a U.S. exchange during my sample period. For Canada, more than 25% of firms listed in the United States get involuntarily delisted. This effect is more pronounced in Nasdaq-listed firms, where more than 40% of Canadian firms eventually get delisted, compared to about 15% of other foreign firms. After controlling for firm characteristics that have an impact on involuntary delistings, such as size, exchange listing, previous year's return, volatility, and leverage, Canadian firms still have a higher propensity to get delisted than other foreign cross-listed firms. However, in a comparison to a U.S. matched sample, there is no statistically significant difference in the likelihood of Canadian firms being delisted, relative to these U.S. firms. These results suggest that Canadian firms may have been treated more similarly to U.S. firms under the U.S. exchanges' rules and enforcement of their continued listing criteria, and that the bonding provided by U.S. exchanges may be stronger for Canadian and U.S. firms. Also, Canadian firms may have fewer impediments to listing in the United States such that small, high-growth Canadian firms have been more able to access U.S. markets compared to foreign firms.
Keywords: G30; G38; 330; Financial markets; International topics; Multinationales Unternehmen; Auslandsniederlassung; Börsennotierung; Going Private; Kanada; USA